The Effect of Underinvestment on the Relationship between Earnings Management and Information Asymmetry - Aulia Fuad Rahman; Mohamat Sabri Hassan; Norman Mohd Saleh; Zaleha Abdul Shukor (Asian Academy of Management Journal of Accounting and Finance, 2013)
Earnings management is often investigated from the opportunistic perspective and rarely from the informational perspective. This study investigates earnings management from the informational perspective by incorporating underinvestment as a moderating variable in the relationship between earnings management and information asymmetry. A panel data regression analysis on firms listed on the Main Board of Bursa Malaysia reveals that earnings management reduces information asymmetry. We also provide evidence that underinvestment moderates the relationship between earnings management and information asymmetry. This finding suggests that earnings management among underinvesting firms reduces information asymmetry. Therefore, underinvestment motivates managers to convey informational earnings management.